US shocks and global exchange rate configurations - Marcel Fratzscher (European Central Bank (ECB), 2007)
The paper analyses the heterogeneity in the link between macroeconomic fundamentals and exchange rates. For a set of important US-specific economic shocks, it shows that such shocks have exerted a remarkably heterogeneous effect on global exchange rate configurations over the past 25 years. Despite a significant decline over time, this heterogeneity remains high as primarily currencies of a few industrialized countries provide the largest contribution to the adjustment of the effective US dollar exchange rate. The paper finds that this heterogeneity is not only due to policy choices of inflexible exchange rate regimes, but to an important extent due to market forces, in particular business cycle synchronization and the degree of financial integration – foremost in portfolio investment – but not to trade. The findings have implications for a potential unwinding of global imbalances and future exchange rate adjustment, as well as for monetary policy choices in emerging market economies.
Keywords: F31; F4; G1; 330; cross-rates; exchange rate; global distribution; heterogeneity; shocks; transmission channels; US dollar; Wechselkurs; Abwertung; Schock; Wechselkurssystem; USA; Welt